Viral Pathogens and Acute Lung Injury: Investigations Inspired by the SARS Epidemic and the 2009 H1N1 Influenza Pandemic - Hendrickson, Carolyn M.; Matthay, Michael A. (Seminars in Respiratory and Critical Care Medicine, 2013)
Acute viral pneumonia is an important cause of acute lung injury (ALI), although not enough is known about the exact incidence of viral infection in ALI. Polymerase chain reaction-based assays, direct fluorescent antigen (DFA) assays, and viral cultures can detect viruses in samples from the human respiratory tract, but the presence of the virus does not prove it to be a pathogen, nor does it give information regarding the interaction of viruses with the host immune response and bacterial flora of the respiratory tract. The severe acute respiratory syndrome (SARS) epidemic and the 2009 H1N1 influenza pandemic provided a better understanding of how viral pathogens mediate lung injury. Although the viruses initially infect the respiratory epithelium, the relative role of epithelial damage and endothelial dysfunction has not been well defined. The inflammatory host immune response to H1N1 infection is a major contributor to lung injury. The SARS coronavirus causes lung injury and inflammation in part through actions on the nonclassical renin angiotensin pathway. The lessons learned from the pandemic outbreaks of SARS coronavirus and H1N1 capture key principles of virally mediated ALI. There are pathogen-specific pathways underlying virally mediated ALI that converge onto a common end pathway resulting in diffuse alveolar damage. In terms of therapy, lung protective ventilation is the cornerstone of supportive care. There is little evidence that corticosteroids are beneficial, and they might be harmful. Future therapeutic strategies may be targeted to specific pathogens, the pathogenetic pathways in the host immune response, or enhancing repair and regeneration of tissue damage.
Keywords: acute respiratory distress syndrome (ARDS); angiotensin-converting enzyme 2 (ACE2); pulmonary edema; alveolar epithelium; lung endothelium